Vulnerability of selected native and invasive woody species to streamflow variability in Western Cape fynbos riparian ecotones - Crous, Casparus Johannes (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2010.